Human gait-labeling uncertainty and a hybrid model for gait segmentation - Wu, Jiaen; Maurenbrecher, Henrik; Schaer, Alessandro; Becsek, Barna; Awai Easthope, Chris; Chatzipirpiridis, George; Ergeneman, Olgac; Pané, Salvador; Nelson, Bradley J. (Frontiers in Neuroscience, 2022)
Motion capture systems are widely accepted as ground-truth for gait analysis and are used for the validation of other gait analysis systems. To date, their reliability and limitations in manual labeling of gait events have not been studied. Objectives: Evaluate manual labeling uncertainty and introduce a hybrid stride detection and gait-event estimation model for autonomous, long-term, and remote monitoring. Methods: Estimate inter-labeler inconsistencies by computing the limits-of-agreement. Develop a hybrid model based on dynamic time warping and convolutional neural network to identify valid strides and eliminate non-stride data in inertial (walking) data collected by a wearable device. Finally, detect gait events within a valid stride region. Results: The limits of inter-labeler agreement for key gait events heel off, toe off, heel strike, and flat foot are 72 ms, 16 ms, 24 ms, and 80 ms, respectively; The hybrid model’s classification accuracy for stride and non-stride are 95.16% and 84.48%, respectively; The mean absolute error for detected heel off, toe off, heel strike, and flat foot are 24 ms, 5 ms, 9 ms, and 13 ms, respectively, when compared to the average human labels. Conclusions: The results show the inherent labeling uncertainty and the limits of human gait labeling of motion capture data; The proposed hybrid-model’s performance is comparable to that of human labelers, and it is a valid model to reliably detect strides and estimate the gait events in human gait data. Significance: This work establishes the foundation for fully automated human gait analysis systems with performances comparable to human-labelers.